Evaluating quality improvement in tertiary care hospital before and after NABH accreditation: a systematic review - Kanyal, Deepika; Ghewade, Babaji (Frontiers in Health Services, 2025)
BackgroundThe National Accreditation Board for Hospitals and Healthcare Providers (NABH.) accreditation process aims to elevate the quality of healthcare services through an impartial, external peer evaluation of an organization's performance. This study compares NABH. quality indicators in a tertiary care hospital before and after accreditation, assessing changes in patient care, hospital management, and staff performance.MethodsA systematic review was conducted following PRISMA guidelines. Literature was searched across PubMed, Scopus, Google Scholar, and the Cochrane Library from August 2023 to January 2024. Keywords included “NABH. accreditation and hospital quality,” “Accreditation in Indian hospitals and patient safety,” and “Tertiary care hospital before and after accreditation.” Boolean operators, synonyms, and related terms were used to ensure comprehensive retrieval. Independent reviewers screened studies, and risk of bias assessment was performed using the Cochrane Risk of Bias Tool.ResultsThe study highlights significant improvements in hospital quality indicators following NABH accreditation. Hospital-acquired infection rates decreased, with infection control compliance improving by 40%. Operational efficiency improved with a 20% reduction in discharge delays and a 15% increase in documentation accuracy. Patient satisfaction scores rose by 25%, and structured policies enhanced service quality by 30%. Additionally, 85% of hospital staff reported higher job satisfaction. Statistical analysis confirmed significant differences in compliance rates (p < 0.05) and patient care metrics (p < 0.01). Despite initial implementation challenges due to resource constraints, the study underscores the need for continuous monitoring and reinforcement of accreditation standards to sustain these improvements.ConclusionNABH accreditation improves patient safety, lowers infection rates, and boosts overall productivity. The structured framework encourages continuous improvement, but institutional commitment and ongoing oversight are necessary for long-term sustainability.